2010
DOI: 10.1016/j.adolescence.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dating violence, substance use and risky sexual behavior among a diverse sample of Illinois youth

Abstract: This study examines the relationship between dating violence, forced sexual intercourse (FSI), and four measures of sexual risk taking (i.e., age at first sex, number of recent (within the last three months) sex partners, alcohol/drug use at last sex, and condom use at last sex) among a sample of 1124 ethnically diverse sexually active adolescents in Illinois. Given conflicting reports regarding the role of gender in dating violence, and the dearth of research examining the role of gender in relations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 24 publications
8
43
1
5
Order By: Relevance
“…Our study further contributes to the body of literature by observing these inconsistencies cross-culturally. However, the findings on self-control and sexual risk taking were consistent with prior research connecting both variables with experiencing and perpetrating relationship violence (Alleyne, Coleman-Cowger, Crown, Gibbons, & Vines, 2011;Finkel et al, 2009;Gover et al, 2008;Raj et al, 2006;Rebellon et al, 2008). Consequently, although there was fairly strong support within and across cultures for selfcontrol theory, the evidence favoring social learning theory was weak within and between samples.…”
Section: Discussionsupporting
confidence: 88%
“…Our study further contributes to the body of literature by observing these inconsistencies cross-culturally. However, the findings on self-control and sexual risk taking were consistent with prior research connecting both variables with experiencing and perpetrating relationship violence (Alleyne, Coleman-Cowger, Crown, Gibbons, & Vines, 2011;Finkel et al, 2009;Gover et al, 2008;Raj et al, 2006;Rebellon et al, 2008). Consequently, although there was fairly strong support within and across cultures for selfcontrol theory, the evidence favoring social learning theory was weak within and between samples.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, Alleyne, Coleman-Cowger, Crown, Gibbons, and Vines (2011) demonstrated that physical dating violence victimization was associated with increased odds of using substances the last time they had intercourse among Hispanic male and female adolescents, with condom use decreasing for Caucasian males who experienced physical dating violence. Among primarily Caucasian high school students, Eaton, Davis, Barrios, Brener, and Noonan (2007) demonstrated a positive association between physical dating violence victimization and number of sexual partners.…”
Section: Dating Violence and Risky Sexual Behaviormentioning
confidence: 99%
“…Risky sexual behavior is prevalent among adolescents (Fergus, Zimmerman, Caldwell, 2007), and may include having sex at a young age (e.g., 15 or younger) (Beadnell, et al, 2005; Hallfors, Iritani, Miller, & Bauer, 2007), having multiple sexual partners (Pflieger, Cook, Niccolai, & Connell, 2013), having sex without a condom (Levy, Sherritt, Gabrielli, Shrier, & Knight, 2009), and using substances (e.g., alcohol, drugs) prior to or during sexual intercourse (Alleyne, Coleman-Cowger, Crown, Gibbons, & Vines, 2011; Seth, Sales, DiClemente, Wingood, Rose, & Patel, 2011). Adolescent risky sexual behavior is associated with an increased risk for the development of sexually transmitted infections (STIs; Niccolai, Ethier, Kershaw, Lewis, Meade, & Ickovics, 2004) and unplanned pregnancies (Bryan, Schmiege, & Magnan, 2012).…”
mentioning
confidence: 99%
“…Ellis et al (2008), por su parte, encontraron entre 646 estudiantes canadienses de noveno grado, que la violencia sexual en el noviazgo se relacionaba con ansiedad, depresión y conductas al margen de la ley. Alleyne et al (2011), en el estudio ya reseñado, hallaron que el haber sido forzado sexualmente por parte de la pareja se relacionaba significativamente con el uso de alcohol y drogas en la última relación sexual.…”
Section: Introductionunclassified